Facilitating Mentally Retarded Students in Learning English Vocabulary Through Rolling Ball Media at SLB BC Sasanti Wiyata Surabaya - Nabilah, Alfufatin (Department of English Language Education, UIN Sunan Ampel Surabaya, 2024)
Each student has different needs and characteristics, and teachers must adapt learning techniques according to the needs and characteristics of students for successful learning. Learning media is one of the methods or tools used in the teaching and learning process. This is done to stimulate learning patterns in order to support the success of the teaching and learning process so that teaching and learning activities can be effective in achieving the desired goals. This also applies when teaching mentally retarded students, teachers can use the media to change information effectively. Rolling ball is one of the media that can be used by teachers in teaching English vocabulary to mentally retarded students. This study aims to describe the use of Rolling Ball Media to facilitate mentally retarded students in learning English vocabulary and to find out what the mentally retarded students’ responses toward the use of Rolling Ball Media in Learning English vocabulary. The subject of this research are the English teacher and mentally retarded students who have experience in teaching English vocabulary using rolling ball media at SLB Sasanti Wiyata Surabaya. The researchers use a descriptive qualitative method. The researchers found that the use of rolling ball learning media has been going well. A rolling ball was used as an evaluation in the vocabulary learning process. By using rolling ball, mentally retarded students can easily remember the vocabulary that has been studied previously because in the rolling ball media there are many game activities that students can do. Learning using 'rolling ball' as a teaching medium can improve the English vocabulary of mentally retarded students. Mentally retarded students can increase the sense of brotherhood between friends and teachers easily and effectively, and also, with this media, mentally retarded students can remember and understand lessons.